Zn‐MOF‐74 as pH‐Responsive Drug‐Delivery System of Arsenic Trioxide. Issue 8 (16th June 2020) - Schnabel, Jennifer; Ettlinger, Romy; Bunzen, Hana
Abstract: Although arsenic and its compounds are mainly known as a poison, they also found applications as drugs in medicine. However, their distribution in a therapeutic dose is often problematic due to their high toxicity. One possibility how to address this issue is utilizing drug‐delivery systems. Herein, we report on a metal‐organic framework (MOF) called Zn‐MOF‐74, which comprises Zn(II) ions and 2, 5‐dihydroxybenzene‐1, 4‐dicarboxylate ligands, as a drug nanocarrier of arsenic trioxide. We synthetized the material in a nanoparticle formulation and showed that due to the open metal sites in Zn‐MOF‐74, it was possible to load the material with a high amount of the As(III)‐drug (in a form of arsenous acid). Moreover, we also investigated the drug release at different pH values. Noticeably, we observed that the As(III)‐release was pH‐triggered and was faster at pH 6.0 than at pH 7.4. Therefore, we suggest Zn‐MOF‐74 as a model example of a MOF containing open metal sites for controlled drug loading and delivery. Abstract : Zn‐MOF‐74 – a framework for drug delivery : Zn‐MOF‐74 is presented as a model example of a MOF containing open metal sites for controlled drug loading and delivery. A neutral drug, here arsenic trioxide, is bound to the unsaturated metal sites of the MOF. Due to the high concentration of the open metal sites, high drug loading can be achieved. Last but not least, a favourable pH‐triggered drug release behaviour – faster at pH 6.0 in comparison to pH 7.4 – was observed.